2006
DOI: 10.1111/j.1462-2920.2006.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community shifts in organically perturbed sediments

Abstract: Bacterial abundance, diversity and sediment function were investigated in organically perturbed sediments under Tasmanian salmon (Salmo salar) farms and adjacent reference sites. Bacterial numbers increased as farming and organic loading progressed through the farm stocking cycle and declined during the fallow period, although not to prestocking levels. Bacterial numbers ranged between approximately 2 x 10(8) and 3 x 10(9) cells per gram of sediment and were higher at cage sites than reference sites. Microelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 31 publications
3
50
1
2
Order By: Relevance
“…Although the primer set gives several mis-hits to phylotypes outside those targeted, it should be noted that all bands sequenced from DGGE gels fell within the target group, indicating that the primers employed did indeed target many of the dominant Flavobacteria in these sediments. Although our counts are subject to uncertainties at several stages of the QPCR process (DNA extraction, PCR, analysis) total bacterial counts are in good agreement to those we reported previously (Bissett et al 2007) as direct counts. Although the absolute numbers are slightly different, the same trends are clear, and at a minimum our QPCR represent good relative counts.…”
Section: Flavobacterial Concentrationssupporting
confidence: 76%
See 3 more Smart Citations
“…Although the primer set gives several mis-hits to phylotypes outside those targeted, it should be noted that all bands sequenced from DGGE gels fell within the target group, indicating that the primers employed did indeed target many of the dominant Flavobacteria in these sediments. Although our counts are subject to uncertainties at several stages of the QPCR process (DNA extraction, PCR, analysis) total bacterial counts are in good agreement to those we reported previously (Bissett et al 2007) as direct counts. Although the absolute numbers are slightly different, the same trends are clear, and at a minimum our QPCR represent good relative counts.…”
Section: Flavobacterial Concentrationssupporting
confidence: 76%
“…This was true for both absolute amounts of Flavobacteria and when their number was considered as a proportion of the total bacterial community, indicating that the increase in flavobacterial DNA was not simply a result of a general increase in all bacteria with farming. Bissett et al (2007) reported SYBR green direct bacterial counts for the same sediment samples. Their results showed the same trend as those revealed by our QPCR results for the total community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally assumed that in these environments the diversity of microbial communities is massive (Torsvik et al 1996) and this diversity leads to a high degree of functional redundancy among microorganisms (Bissett et al 2007).…”
Section: Introductionmentioning
confidence: 99%